RUANG KEBUGARAN DI PLUIT - Jonea Kane Darmanto; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2020)
Urban where life is full of busyness, forcing people to choose to do everything instantly. Problems that arise include the absence of a social life and lifestyle that does not support the quality of public health. According to a Zipjet Company survey, Jakarta is categorized as the most stressful city and has an impact on deteriorating health and quality of life. Open Architecture is an architectural proposal that discusses The Third place or an intermediate space that is expected to serve the needs of modern urban society. Pluit, North Jakarta one of the areas that has a third place character. The location directly adjacent to the first place and second place in PLuit is one of the reasons for site selection, so presenting a third place project here is expected to be a solution to the regional problem. Projects that provide a platform for the community to be able to come entertain themselves for a moment from the busyness or problems they face. Prioritizing sports programs with the intention of increasing interest in health, with the concept of wellness that is also adjusted to the needs of the surrounding community. So that this project becomes a place of fatigue that also supports the improvement of quality of life. With sports, an activity which in its development can be carried out as an entertaining and enjoyable activity, individuals between individuals can also meet and have the same motivation so that it can also create a community that further strengthens social life among surrounding communities. Abstrak Perkotaan dimana kehidupan di penuh kesibukan, memaksa masyarakat memilih untuk melakukan semua hal dengan instan. Permasalahan yang muncul antara lain adalah tidak adanya kehidupan bersosialisasi dan pola hidup yang kurang mendukung kualitas kesehatan masyarakat. Menurut sebuah survey Perusahaan Zipjet (2017), Jakarta masuk dalam kategori kota paling stres dan berdampak pada kemerosotan kesehatan serta kualitas hidup. Open Architecture adalah sebuah proposal arsitektur yang membahasa mengenai The Third place atau ruang antara yang diharapkan mampu melayani kebutuhan masyarakat kota modern. Pluit, Jakarta Utara salah satu daerah yang memiliki karakter third place. Lokasi yang berbatasan langsung dengan first place dan second place di PLuit ini menjadi salah satu alasan pemilihan tapak, Sehingga menghadirkan proyek third place disini diharapkan menjadi solusi permasalahan kawasan. Proyek yang memberi wadah bagi masyarakat untuk bisa datang menghibur diri sejenak dari kesibukan atau masalah yang di hadapinya. Mengutamakan program olahraga dengan maksud meningkatkan minat terhadap kesehatan, dengan konsep wellness yang di sesuaikan juga dengan kebutuhan masyarakat sekitar. Sehingga proyek ini menjadi sebuah tempat pelepas penat yang sekaligus mendukung peningkatan kualitas hidup. Dengan adanya olahraga, sebuah kegiatan yang dalam perkembanganya dapat dilakukan sebagai kegiatan yang menghibur dan menyenangkan, individu antar individu juga dapat bertemu dan memiliki motivasi yang sama sehingga dapat pula tercipta sebuah komunitas yang semakin mempererat kehidupan sosial antar masyarakat sekitar.